基于智慧屏重症监护室服务模式的探索. - 何秋煜; 杨 帅; 孔丽丽; 梁雪妃; 王芳芳; 张晓璇 (Chinese Nursing Research, 2025)
To explore the ICU service model based on smart screen from the system organization and professional medical and nursing levels. To enhance the quality of service and work efficiency of medical staff during various periods of patient hospitalization. To achieve the intelligence and digitization of ICU services.